Mitochondria in Pathological Cardiac Hypertrophy Research and Therapy - Yang, Dan; Liu, Han-Qing; Liu, Fang-Yuan; Guo, Zhen; An, Peng; Wang, Ming-Yu; Yang, Zheng; Fan, Di; Tang, Qi-Zhu (Frontiers in Cardiovascular Medicine, 2022)
Cardiac hypertrophy, a stereotypic cardiac response to increased workload, ultimately progress to severe contractile dysfunction and uncompensated heart failure without appropriate intervention. Sustained cardiac overload inevitably results in high energy consumption, thus breaking the balance between mitochondrial energy supply and cardiac energy demand. In recent years, accumulating evidence has indicated that mitochondrial dysfunction is implicated in pathological cardiac hypertrophy. The significant alterations in mitochondrial energetics and mitochondrial proteome composition, as well as the altered expression of transcripts that have an impact on mitochondrial structure and function, may contribute to the initiation and progression of cardiac hypertrophy. This article presents a summary review of the morphological and functions changes of mitochondria during the hypertrophic response, followed by an overview of the latest research progress on the significant modulatory roles of mitochondria in cardiac hypertrophy. Our article is also to summarize the strategies of mitochondria-targeting as therapeutic targets to treat cardiac hypertrophy.